Study on the cavity closure behavior of steel ingots during open die forging. (November 2019) - Kwon, Yongchul; Kim, Sangsik; Kang, Jonghun
The manufacturing of sound forgings from large steel ingots requires that internal cavity defects generated during the steel ingot solidification process be compressed by open die forging. The forging ratio that is generally recommended to remove internal defects in large forged products is 3S (threefold); however, the practice lacks a theoretical basis. In this study, a forging experiment and a finite element analysis were performed to investigate the correlation between the forging ratio for large steel ingots (3S) and the cavity closure behavior. First, a hot compression experiment was performed by varying the temperature and strain rate, and the flow stress data observed in the experiment was applied to the finite element analysis. In the experiment for the cogging process, the forging ratio was applied to an actual non-compressive defect material. The finite element analysis was performed using the same forging path as the forging experiment. In the cogging experiment, cavity closure was found by ultrasonic inspection at the forging ratio of 2.9S. The finite element analysis showed that the size of the cavity was significantly decreased at the forging ratio of 2.9S. A finite element analysis was also performed to investigate effective strain and hydrostatic stress at the forging ratio of 2.9S. Finally, this article provides the theoretical basis for the limitation of the internal defect size in initial materials, the threshold effective strain, and the limiting forging ratio of forged products to ensure the internal soundness of large forged products.